How does collaborative governance evolve? Insights from a medium-n case comparison. Issue 4 (29th May 2020) - Ulibarri, Nicola; Emerson, Kirk; Imperial, Mark T; Jager, Nicolas W; Newig, Jens; Weber, Edward
Abstract: Understanding the performance of collaborative governance regimes (CGRs) necessitates an understanding of how stakeholders and their interactions evolve over time. However, few studies assess the evolution of the structure or process dynamics of CGRs over time. This paper contributes to our understanding of the longitudinal dynamics of CGRs. We apply a modified grounded theory approach to a dataset of collaboration case studies to develop empirically-based theory about how often CGRs persist over time, how different components of CGRs evolve over time, what conditions support or hinder this evolution, and how different developmental trajectories lead to differences in the outputs and outcomes achieved by these groups. We find that CGRs follow a variety of trajectories, from failing to initiate, to achieving their work in a relatively quick time, to sustaining their operations for decades, to incurring slow or rapid declines in health. Additionally, many characteristics of CGRs, including leadership, collaborative process, accountability, and outputs/outcomes, peak at the midpoint of the observed time, suggesting that at some point, even stable and healthy collaborations incur some decline in their robustness. As an exploratory study, this work highlights the need for a better accounting of how CGRs develop, sustain, evolve, and decline over time.